Fluorofenidone attenuates interleukin‐1β production by interacting with NLRP3 inflammasome in unilateral ureteral obstruction. Issue 6 (10th June 2018) - Zheng, Linfeng; Zhang, Jin; Yuan, Xiangning; Tang, Juan; Qiu, Sisi; Peng, Zhangzhe; Yuan, Qiongjing; Xie, Yanyun; Mei, Wenjuan; Tang, Yiting; Meng, Jie; Hu, Gaoyun; et al.
Abstract: Aim: We explored whether Fluorofenidone reduced interleukin‐1β (IL‐1β) production by interacting with NLRP3 inflammasome in unilateral ureteral obstruction (UUO). Methods: Ureteral obstruction rats were treated with Fluorofenidone (500 mg/kg per day) for 3, 7 days. Morphologic analysis and leukocytes infiltration were assessed in ligated kidneys. Furthermore, plasmids of NLRP3, ASC, pro‐Caspase‐1, pro‐IL‐1β were co‐transfected into 293 T cells, and then treated with Fluorofenidone (2 mM). The expression of NLRP3, ASC, pro‐caspase‐1, cleavage caspase‐1, pro‐IL‐1β and cleavage IL‐1β were measured by Western blot or real‐time PCR in vi vo and in vitro . Moreover the interaction of NLRP3 inflammasome‐assembly was detected by co‐immunoprecipitation and confocal immunofluorescence. Results: Fluorofenidone treatment significantly attenuated renal fibrosis and leukocytes infiltration in UUO model. Fluorofenidone had no effect on the expression of pro‐IL‐1β. Interestingly, Fluorofenidone inhibited the activation of NLRP3 inflammasome, downregulated Caspase‐1 levels and thereby decreased the cleavage of pro‐IL‐1β into IL‐1β in vivo and in vitro . Fluorofenidone treatment distinctively weakened the interaction between NLRP3 and ASC, as well as ASC and pro‐Caspase‐1 in vivo . However, Fluorofenidone treatment only significantly weakened the interaction between ASC and pro‐Caspase‐1 in co‐transfected 293 T cells. Conclusion: Fluorofenidone serves as a novel anti‐inflammatory agent that attenuates IL‐1β production in UUO model by interacting with NLRP3 inflammasome. Summary at a Glance: An interesting manuscript which investigates whether fluorofenidone (one of the pyridine agents) could ameliorate kidney fibrosis process in UUO model by regulating the interaction of NLRP3 inflammasome‐assembly and the inhibition of IL‐1B production.